Two women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women seated at staggered heights. The woman in back is leaning down with her cheek touching the other woman's face and her right arm resting on the other woman's right shoulder. Her left hand is holding onto the second woman's upper left arm. The second woman has her left arm draped over the first woman's knee.